RECONSTRUCTION OF MARRIAGE ZONATION IN ISLAMIC LAW PERSPECTIVE - Alam, Syariful (Faculty of Law, University of Muhammadiyah Malang, 2019)
Zoning, a limitation system that is so widely discussed today, focuses initially on the education system in Indonesia, namely on the problem of admission of new students which began in 2017. One of these policy settings is for children to be educated in areas close to residence. This system is often connected by the public with the search for a partner to get married. Based on normative Islamic law research, marriage in Islam does not provide specific restrictions regarding this zoning in finding a partner. However, this zoning can be implicit in the recommendations of marriage in Islam. Bringing up conflict that has become a topic of discussion in many media and communities, which in the end, can create a solution for couples who find it difficult to find a life partner as well as presenting internal conflicts that pertain to the realm of privacy, intersect with the right of humans to freely choose from and where their partners. Regardless of a marriage that leads to the coercion of one partner or coincidence of finding the right partner according to the zoning where the couple lives.